State Audit Digitization and Green Technology Innovation in State-Owned Enterprises - Chunhui You; Jing Wang (SAGE Open)
Based on a quasi-natural experiment on the acceptance of China’s Golden Auditing Project II, this study investigates the impact of state audit digitization on the green technology innovation of SOEs and its mechanism using the difference-in-difference model. First, state audit digitization significantly improves the level of green technology innovation in SOEs, and this role is time-differentiated from green invention patents and green utility models. Second, the results of the heterogeneity test show that the facilitating effect of state audit digitization is reflected mainly in heavily polluting SOEs and central SOEs. Third, the influence mechanism test results found that state audit digitization promotes the green technology innovation of SOEs through R&D investment and subsidy channels, and the mediation effect of the environmental regulation channel is not significant. This study broadens the research related to the economic consequences of state audit digitization and the influencing factors of enterprises’ green technology innovation and reveals the significance of audit digital transformation.